Climate change as a global problem of modernity: challenges and ways of solving (philosophical as-pect) - Матюхіна, О. А.; Павлюк, Н. Ю. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
Reasons of anthropogenic character, that resulted in the global problem of change of climate, are investigated in the article. It is underlined that globalization economic, scientific, political spheres of the modern world created terms for the acceptance of global measures in decision of problem of change of climate and the actions of world community, sent to the decision of this problem, are examined.